The Trend Ethnopedagogy Research as Contribution in Elementary Science Learning in The Era of Industrial Revolution 4.0 - Ibrahim, Ibrahim; Suranti, Ni Made Yeni (Jurnal Ilmiah Profesi Pendidikan, 2024)
Ethnopedagogy is an approach to education that uses students' culture and cultural context as a basis for the learning process. Ethopedagogy is important because it helps shape individuals who are not only academically intelligent but also have a strong moral and ethical awareness, which is very necessary to face the complex challenges in today's global society. This research aims to identify and analyze ethnopedagogical research trends in their contribution to elementary school science learning in the era of revolution 4.0. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed included types of publications, authors on ethnopedagogy, sources of publications, and titles of research on ethnopedagogy that were widely cited. The data analysis method uses bibliometric analysis assisted by VOSviewer software. The results of the analysis show that the trend of ethnopedagogical research indexed by Google Scholar from 2015 to 2024 has experienced a fluctuating increase. The biggest increase was from 2020 to 2021, then decreased in 2022. There are many documents in the form of articles, proceedings, or edited books that discuss ethnopedagogy research. Key words that are often used in ethnopedagogical research are culture, local wisdom, local wisdom, ethnopedaogical values, and learning process.